2014
DOI: 10.3904/kjim.2014.29.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of gastric variceal obliteration usingN-butyl-2-cyanoacrylate in patients with acute gastric variceal hemorrhage

Abstract: Background/AimsTo evaluate the long-term efficacy and safety of endoscopic injection of N-butyl-2-cyanoacrylate (NBC; Histoacryl) for treatment of bleeding gastric varices.MethodsWe retrospectively analyzed the records of 455 patients with gastric variceal hemorrhage (GVH) who were consecutively treated with NBC from January 2004 to July 2013, with a mean follow-up period of 582 days. The patients' endoscopic findings, initial hemostasis, complications, rebleeding rates, and bleeding-related death rates were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 23 publications
3
24
0
1
Order By: Relevance
“…[5,6] Most of the available information about upper gastrointestinal ectopic variceal bleeding control is acquired from case reports or small case series. Randomized controlled trials have also not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[5,6] Most of the available information about upper gastrointestinal ectopic variceal bleeding control is acquired from case reports or small case series. Randomized controlled trials have also not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some studies have demonstrated close association between Child-Pugh scores and recurrent bleeding risk of variceal bleeds that ceased spontaneously or as a result of treatment [22, 23]. Distribution of patients according to groups based on Child-Pugh stages revealed that cirrhotic patients in Child A stage were more numerous in all groups with gastric varices.…”
Section: Discussionmentioning
confidence: 90%
“…Our study found that patients with EVs+ GOV2 with GOV1 had an increased risk of rebleeding at 1 year, and EVs+ GOV2 with GOV1 was identi ed as an independent risk factor (OR=31.063, 95% CI: 1.560-618.4).Kang EJ et al reported the incidence of rebleeding incident of in patients with liver cancer (P<0.001) and GOV2 (P=0.009) was signi cantly increased at 1-year when comparing the prognosis of 127 GV patients (GOV1:GOV2: IGV=56:61:10) who had been treated with tissue glue for preventing rebleeding (23). Jun CH et al retrospectively analyzed reported 455 GVs patients after endoscopic treatment showed that no different in rebleeding for 1-year between the GOV1 and GOV2 (24), however, the comparing between EV+GOV2 without GOV1 group and EV+GOV2 with GOV1 group was not complete. We found a signi cant difference in the incidence of rebleeding at 1-year between EV+GOV2 without GOV1 group and EV+GOV2 with GOV1 group.…”
Section: Discussionmentioning
confidence: 99%